1998
DOI: 10.1073/pnas.95.12.6995
|View full text |Cite
|
Sign up to set email alerts
|

A physiological role of the adenosine A 3 receptor: Sustained cardioprotection

Abstract: Adenosine released during cardiac ischemia exerts a potent, protective effect in the heart. A newly recognized adenosine receptor, the A 3 subtype, is expressed on the cardiac ventricular cell, and its activation protects the ventricular heart cell against injury during a subsequent exposure to ischemia. A cultured chicken ventricular myocyte model was used to investigate the cardioprotective role of a novel adenosine A 3 receptor. The protection mediated by prior activation of A 3 receptors exhibits a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
149
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 197 publications
(153 citation statements)
references
References 19 publications
4
149
0
Order By: Relevance
“…In an effort to develop potent agonists and antagonists for A 3 ARs, a wide range of N 6 -and 2′-substituted adenosine derivatives have recently been pharmacologically characterized [8][9][10]. We found that various adenosine derivatives, which were previously demonstrated to be agonists at A 1 and A 2A ARs and assumed to be full/partial agonists at A 3 ARs, are indeed antagonists at this subtype.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…In an effort to develop potent agonists and antagonists for A 3 ARs, a wide range of N 6 -and 2′-substituted adenosine derivatives have recently been pharmacologically characterized [8][9][10]. We found that various adenosine derivatives, which were previously demonstrated to be agonists at A 1 and A 2A ARs and assumed to be full/partial agonists at A 3 ARs, are indeed antagonists at this subtype.…”
Section: Introductionmentioning
confidence: 78%
“…For A 3 AR binding experiments, the procedures used were similar to those previously described [17]. Briefly, each tube contained 100 μL of membrane suspension (20 μg protein), 50 μL of [ 125 I]I-AB-MECA (final concentration 1.0 nM), and 50 μL of increasing concentrations of compounds in Tris-HCl buffer (50 mM, pH 8.0) containing 10 mM MgCl 2 , 1 mM EDTA.…”
Section: Radioligand Binding Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…13 Cardioprotection by selective A 3 AR agonists has been extensively explored in various species. [14][15][16] Other selective A 3 AR agonists have recently been reported, based on introduction of large substituents at the N 6 and C2 positions and modification of the ribose ring, particularly at the 4′ and 5′ positions. 16-19 For example, the 4′ -thio analogue 2 is among the most selective known A 3 AR agonists,17 and 3′ -amino substitution is possible.…”
mentioning
confidence: 99%